The Impact of Online Games On Students In Learning English Vocabulary - Illona Beatrice Ta'uno; Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2022)
English vocabulary is one of the basic types of knowledge that must be masteredby EFL in learning English. With the rapid changing and development of globalization, vocabulary learning nowadays can be done through various media, one of them is through online games. Online games are the games that are very popular among students todays due to this kind of circumstances and one of these online games is Mobile Legends. The purpose of this study is to find out the impacts of an online game which is Mobile Legends in English Vocabulary learning in SMA GKST 2 Tentena. In this study, the subjects are the 12 students from 4 classes. The method used in this study is descriptive quantitative and usesinstruments in the form of questionnaires, tests, and interviews. Based on the data obtained, this study found that online game which is Mobile Legends have an impact in students to achieve good results in learning English vocabulary.